2023
DOI: 10.1177/18333583231151979
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clinical note format on diagnostic accuracy and efficiency

Abstract: Background Clinician notes are structured in a variety of ways. This research pilot tested an innovative study design and explored the impact of note formats on diagnostic accuracy and documentation review time. Objective To compare two formats for clinical documentation (narrative format vs. list of findings) on clinician diagnostic accuracy and documentation review time. Method Participants diagnosed written clinical cases, half in narrative format, and half in list format. Diagnostic accuracy (defined as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Several authors Payton et al, 2023; 2023) reported the need for balance between structured and narrative forms of documentation and that highly structured formats (a feature of EHRs) can limit usability. Several authors highlighted multifactor influences on CDI, including personal, systemic and environmental Lövestam et al, 2022;.…”
Section: Theme 2 Processesmentioning
confidence: 99%
See 3 more Smart Citations
“…Several authors Payton et al, 2023; 2023) reported the need for balance between structured and narrative forms of documentation and that highly structured formats (a feature of EHRs) can limit usability. Several authors highlighted multifactor influences on CDI, including personal, systemic and environmental Lövestam et al, 2022;.…”
Section: Theme 2 Processesmentioning
confidence: 99%
“…Standardisation to address CDI-related issues (e.g. ambiguous terminology, inconsistent, incomplete and variability in diagnosis documentation) was recommended by Alonso et al (2020) and Payton et al (2023). described issues arising from documentation that is ambiguous when terms such as "probable," "likely" and "query" are used.…”
Section: Theme 2 Processesmentioning
confidence: 99%
See 2 more Smart Citations